Challenges and opportunities for improving N use efficiency for rice production in sub-Saharan Africa - Tsujimoto, Y.; Rakotoson, T.; Tanaka, A.; Saito, Kazuki (Informa UK Limited, 2019)
In sub-Saharan Africa (SSA), rice production from smallholder farms is challenged because of a lack of fertilizer inputs and nutrient-poor soils. Therefore, improving nutrient efficiency is particularly important for increasing both fertilizer use and rice yield. This review discusses how to improve the return from fertilizer input in terms of agronomic N use efficiency (AEN), that is, the increase in grain yield per kg of applied N, for rice production in SSA. The AEN values we summarized here revealed large spatial variations even within small areas and a certain gap between researcher-led trials and smallholder-managed farms. Experimental results suggest AEN can be improved by addressing spatial variations in soil-related factors such as P, S, Zn, and Si deficiencies and Fe toxicity in both irrigated and rainfed production systems. In rainfed production systems, differences in small-scale topography are also important which affects AEN through dynamic changes in hydrology and variations in the contents of soil organic carbon and clay. Although empirical evidence is further needed regarding the relationship between soil properties and responses to fertilizer inputs, recent agricultural advances have generated opportunities for integrating these micro-topographical and soil-related variables into field-specific fertilizer management. These opportunities include UAV (unmanned aerial vehicle) technology to capture microtopography at low cost, database on soil nutrient characteristics at high resolution and more numbers of fertilizer blending facilities across SSA, and interactive decision support tools by use of smartphones on site. Small-dose nursery fertilization can be also alternative approach for improving AEN in adverse field conditions in SSA.ABBREVIATIONS: AEN: agronomic nitrogen use efficiency; FISP: farm input subsidy program; VCR: value cost ratio; SOC: soil organic carbon; SSA: sub-Saharan Africa; UAV: unmanned aerial vehicle